复合电极材料及其制备方法 (2018)
本发明提供了种复合电极材料及其制备方法。所述复合电极材料包括依次设置的碳基薄膜、多孔金属层和电化学活性物质层，其中，所述电化学活性物质层在所述多孔金属层表面原位生长形成。所述复合电极材料的制备方法，包括以下步骤：提供碳基薄膜，采用电镀法在所述碳基薄膜表面沉积多孔金属，制备多孔金属层；在所述多孔金属层表面原位生长电化学活性物质，制备电化学活性物质层。 The invention provides a composite electrode material and a preparing method thereof. The composite electrode material comprises a carbon-based film, a porous metal layer and an electrochemical activity substance layer, wherein the carbon-based film, the porous metal layer and the electrochemical activity substance layer are sequentially arranged; the electrochemical activity substance layer is formed in an in-situ-growth mode on the surface of the porous metal layer. The preparing method of the composite electrode material includes the following steps that the carbon-based film is provided, porous metal is deposited on a surface of the carbon-based film with the electroplating method, and the porous metal layer is prepared; electrochemical activity substances grow on the surface of the porous metal layer in an in-situ mode, and the ele